De l’activité à l’expérience - Michel Récopé; Stéphane Héros; Simon Boyer; Simon Flandin; Géraldine Rix-Lièvre (Revue d'anthropologie des connaissances)
This contribution presents the theoretical and methodological constructs of a situated cognitive anthropology focusing on activity and experience of high-level athletes, with training purpose. Grounded in a relational and normative ontology, it is characterized by (i) a theory of experience, conceptualizing three levels: the in situ living experience, the post-situation lived experience, and the very experience, (ii) a methodology of activity analysis finalized by the identification of different regularities brought into perspective: observable paired regularities of behaviors and circumstances, and regularities of lived experiences, and (iii) the identification of sensitivity to... as a prevailing norm of activity, guiding the activities of a person in the studied socio-cultural domain. Two studies are presented: one conducted in volleyball, the other in football. In conclusion, we discuss the theoretical and methodological contribution of such a perspective to embodied and situated cognition approaches.